GEN Z’S IMPULSE BUYING BEHAVIOR OF SHOPPING THROUGH LIVE-STREAMING SOCIAL COMMERCE PLATFORMS:: Investigating the Role of Parasocial Interaction and Social Commerce Emotional Motivation - Mardhiana, Hasna Rizki (jfpublisher, 2024)
In social commerce, consumers receive emotional motivation to purchase products because they feel familiar and bonded with the promoter, often losing track of time and self-awareness in a flow state, leading to impulse buying. As Gen Z are often presents more tendency toward impulse shopping behaviors compared to other generations, this study aims to investigate the impulse buying behavior of Generation Z (Gen Z) on live-streaming social commerce platforms, focusing on the roles of Parasocial Interaction (PSI) and Social Commerce Emotional Motivation (SCEM). Using a quantitative approach, data were collected via online surveys from individuals born between 1998 and 2007 who had made at least two unplanned purchases after watching live-streamed shopping events within four weeks. Statistical regression analysis was conducted using IBM SPSS 26.0 to explore the relationships between PSI, SCEM, and impulse buying behavior (IBB). The findings reveal that both PSI and SCEM significantly influence IBB among Gen Z consumers. Strong parasocial relationships with live-stream hosts enhance trust and connection, while emotional engagement through SCEM motivates spontaneous purchases. The study highlights the synergistic effect of PSI and SCEM, suggesting that a combined approach is most effective in driving impulse buys. This study contributes to the understanding of consumer behavior in the context of emerging social commerce trends, providing actionable insights for enhancing marketing strategies targeted at Gen Z.